(untitled) (Вісник: Міжнародні відносини, 2024)
Mali is a country in the Sahel with significant economic potential, which is at the epicenter of the struggle between separatists and government troops, nomadic tribes and farmers, terrorists and the troops of France and the UN, Western countries, Russia and Turkey. However, the participation of the world community in the settlement of this conflict is characterized by low effectiveness, so the author is trying to find out why Mali cannot become a stable country.